Prognostic indicators in primary plasma cell leukaemia: a multicentre retrospective study of 117 patients. (7th January 2018) - Jurczyszyn, Artur; Radocha, Jakub; Davila, Julio; Fiala, Mark A.; Gozzetti, Alessandro; Grząśko, Norbert; Robak, Paweł; Hus, Iwona; Waszczuk‐Gajda, Anna; Guzicka‐Kazimierczak, Renata; Atilla, Erden; Mele, Giuseppe; et al.
Abstract : We report a multicentre retrospective study that analysed clinical characteristics and outcomes in 117 patients with primary plasma cell leukaemia (pPCL) treated at the participating institutions between January 2006 and December 2016. The median age at the time of pPCL diagnosis was 61 years. Ninety‐eight patients were treated with novel agents, with an overall response rate of 78%. Fifty‐five patients (64%) patients underwent upfront autologous stem cell transplantation (ASCT). The median follow‐up time was 50 months (95% confidence interval [CI] 33; 76), with a median overall survival (OS) for the entire group of 23 months (95% CI 15; 34). The median OS time in patients who underwent upfront ASCT was 35 months (95% CI 24·3; 46) as compared to 13 months (95% CI 6·3; 35·8) in patients who did not receive ASCT ( P  =   0·001). Multivariate analyses identified age ≥60 years, platelet count ≤100 × 10 9 /l and peripheral blood plasma cell count ≥20 × 10 9 /l as independent predictors of worse survival. The median OS in patients with 0, 1 or 2–3 of these risk factors was 46, 27 and 12 months, respectively ( P  <   0·001). Our findings support the use of novel agents and ASCT as frontline treatment in patients with pPCL. The constructed prognostic score should be independently validated.